Cultural Studies: Theory and Practice - Barker, Chris (SAGE Publications, 2008)
The leading undergraduate introduction to cultural studies. It takes the student through all they need to know: the theoretical foundations and developments of cultural studies and the questions that occupy the field today, from the multiple meanings of 'culture' itself to ideology, language, subjectivity, sex, space, race, media, the urban, youth and resistance.